Formulasi Pangan Darurat Berbentuk Food Bars Berbasis Tepung Millet Putih (Panicum milliaceum L.) dan Tepung Kacang Merah (Phaseolus vulgaris L.) - Raden Baskara Katri Anandito; Siswanti Siswanti; Edhi Nurhartadi; Rini Hapsari (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2016)
This study aimed to obtain a formula emergency food in the form food bars made from white millet flour and red bean flour. Foodbars made with Intermediate Moisture Food (IMF) technology with wet dyeing technique. This study used completely randomized design (CRD), which consists of a single factor, namely the variation formula white millet flour and red bean flour. The results showed that the formula food bars with the highest level of consumer acceptance in the composition of 15 g of white millet flour, red bean flour 10 g, 2 g sugar, 10 g margarine, milk full cream 13 g, 6.043 g and the addition of water. In 100 g of food bars contained water, ash, protein, fat, carbohydrate, and caloric value a respectively of 16.45%, 1.45%, 10.99%, 35.39%, 42.26%, 0 , 81 and 233.80 kcallbar.ABSTRAKPenelitian ini bertujuan untuk memperoleh formula pangan darurat berbentuk food bars berbahan dasar tepung millet putih dan tepung kacang merah. Food bars dibuat dengan teknologi Intermediate Moisture Food (IMF) dengan teknik pencelupan basah. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) yang terdiri dari satu faktor yaitu variasi formula tepung millet putih dan tepung kacang merah (15:10; 12,5:12,5; 10:15). Hasil penelitian menunjukkan bahwa formula food bars dengan tingkat penerimaan konsumen tertinggi pada komposisi tepung millet putih 15 g, tepung kacang merah 10 g, gula halus 2 g, margarine 10 g, susu full cream 13 g, dan penambahan air 6,043 g. Dalam 100 g food bars terkandung air, abu, protein, lemak, karbohidrat nilai a dan kalori berturut-turut sebesar 16,45%,1,45%, 10,99%, 35,39%, 42,26%, 0,81 dan 233,80 kkallbar.